Management Analysis of Pharmacy Supplies at Bhayangkara Hospital Third Class Pekanbaru Pharmacy Installation in Riau Regional Police 2018 - Vatri Wahyuni (Jurnal Kesehatan Komunitas, 2020)
Supplies are a number of materials or goods provided by the Hospital, both in the form of finished goods, raw materials, or all related items for the smooth running of the Hospital to meet patient requests. The aim of the study was to analyze the process of managing pharmaceutical supplies in the Pharmacy Installation of Bhayangkara TK III Pekanbaru Polda Riau Hospital. This type of research is a descriptive study with a qualitative method approach, carried out at Bhayangkara Hospital, Riau Regional Police with a total of 7 informants. This research was conducted by conducting in-depth interviews and field observations and document review, and data processing was done by data triangulation. From the results of the study it was found that the selection, planning, procurement, receipt, storage, distribution, control, deletion and administration of drug supplies in general has not gone well, but some obstacles experienced were in the selection of drugs determined by doctors, drugs often used by doctors drugs that are not available in the hospital or outside the formulary due to lack of human resources, preparation of drugs not in accordance with alphabet, found there is an error in distributing drugs to rooms, PJ Room that does not want to return drugs that are not used so that there is a buildup of drugs that expire in the room and not returned to the drug warehouse, there was no special team for drug management so that when the drug stock was lacking, the pharmacists bought it at a nearby pharmacy located near the hospital. For this reason, the management of pharmaceutical supplies is given more attention, especially in the field of pharmacy, in accordance with alphabets, drugs are always available and used by doctors, expired drugs are reduced every year and stock cards are filled every day